Norway : Financial System Stability Assessment-Press Release; and Statement by the Executive Director for Norway. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
Much of the work of the Financial Sector Assessment Program (FSAP) was conducted prior to the COVID-19 pandemic, with the missions ending on February 13, 2020. Given the FSAP's focus on medium-term challenges and vulnerabilities, however, its findings and recommendations for strengthening policy and institutional frameworks remain pertinent. The report was updated to reflect key developments and policy changes since the mission work was completed. It also includes a risk analysis that quantifies the possible impact of the COVID-19 crisis on bank solvency. Since the previous FSAP in 2015, the Norwegian authorities have taken welcome steps to strengthen the financial system. Regulatory capital requirements for banks were raised and actions were taken to bolster the weak capital position of insurers. Alongside other macroprudential measures, temporary borrower-based measures for residential mortgages were introduced, which seem to have had some moderating impact on segments of the housing market. The resolution framework was also strengthened, with the implementation of the Bank Recovery and Resolution Directive (BRRD) and the designation of Finanstilsynet (FSA) as the resolution authority.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet